(untitled) (Al-Academy, 2025)
Graffiti art, despite being a relatively modern form, has recently gained notable prominence and influence among artists. This study explores graffiti in Mosul through four chapters. The first addresses the research problem, significance, objectives, and scope, along with definitions of key terms. The theoretical framework examines the concept, techniques, and characteristics of graffiti art. The methodology employs a descriptive–analytical approach, analyzing four selected works by young Mosul graffiti artists from distinct urban locations, including the Old City, the “Jar Carrier Roundabout”, and the “Al-Muthanna Overpass”. The study concludes with findings, conclusions, and recommendations, emphasizing the role of graffiti as a visual and cultural expression within the public sphere.